Factores asociados a la percepción de calidad de parto en puérperas atendidas en el Hospital Iquitos César Garayar García, 2022 - Ruiz Saldaña, Claudia Cristina (2023)
The time after birth is a very important time, since most medical problems related to the newborn and the mother occur during this period. If the birth experience is positive, it can help a woman grow personally, improve her self-esteem, and succeed in her role as a mother. On the other hand, if the experience is negative, it can increase the risk of health problems for both mother and baby. For this reason, the present work aims to determine the factors associated with the perception of quality of delivery in puerperal women treated at the Hospital Iquitos "César Garayar García", 2022. For this, an observational-analytical study was developed, with 135 pregnant women as a sample. . Concluding that regarding the social characteristics of women who come from urban areas (OR=0.4,p=0.017), are from peri-urban areas (OR=2.4,p=0.036) and only have primary education (OR=3 .7, p=0.041) are more likely to feel dissatisfaction with the quality of care during childbirth. Social characteristics such as work activity, economic support from the partner and family, living with the partner and consumption of harmful substances did not present a significant association with the perception of dissatisfaction (p>0.05). In the psychological component, it was observed that the emotional support of the family is associated with a lower perception of dissatisfaction during childbirth (OR=0.3, p<0.001). Obstetric characteristics such as parity, history of abortion, deceased children and the adequate number of prenatal check-ups did not present a significant association with the perception of dissatisfaction during childbirth (p>0.05).